2019
DOI: 10.4012/dmj.2018-352
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of zinc-containing desensitizer on bacterial biofilm formation and root dentin demineralization

Abstract: This study compared the effect of a novel zinc containing, Caredyne Shield (CS), and a fluoroaluminocalciumsilicate-based, Nanoseal (NS) desensitizers on dentin tubule occlusion, inhibition of Streptococcus mutans (S. mutans) biofilm growth, and resistance to bacterial demineralization. Desensitizers were applied to simulated hypersensitive bovine dentin, with distilled water used as a control. S. mutans biofilms were grown on the surface of each specimen in an oral biofilm simulator. CS showed the least bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…For caries, Rahman et al reported that if calcium in hydroxyapatite crystals is replaced by zinc, the solubility of hydroxyapatite crystals will be increased [7]. On the other hand, Saad et al [9] reported in their in vitro study that zinc inhibited the formation of biofilm and dentin demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…For caries, Rahman et al reported that if calcium in hydroxyapatite crystals is replaced by zinc, the solubility of hydroxyapatite crystals will be increased [7]. On the other hand, Saad et al [9] reported in their in vitro study that zinc inhibited the formation of biofilm and dentin demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Although the SS group exhibited nearly the same failure mode as that in the Cont(#4000), it is not currently known why the bond strength was lower. In the CS group, it is thought that deposited calcium fluoride or calcium phosphate or released zinc ions [24][25][26][27] may have suppressed the etching effect of the acidic monomer of the bonding resin 26) , thereby decreasing the bonding strength, demonstrating the failure at the interface between the dentin and the bonding resin. However, the NS group exhibited nearly the same bond strength and failure mode (cohesive failure inside the bonding resin, cohesive failure inside the resin and cohesive failure inside the dentin) as in the Cont(#4000) group, and the interfacial failure was found in some specimens.…”
Section: Bond Strength Immediately After Application and 7 Days Latermentioning
confidence: 99%
“…It acts as a desensitizer by inducing chemical occlusion of dentinal tubules and contains a novel functional filler which releases not only ions like calcium or fluorine but also zinc. Zinc is reported to reduce the demineralization of enamel and dentin, and inhibit dentin collagen degradation, plaque growth and biofilm formation (12,13).…”
Section: Introductionmentioning
confidence: 99%